АВТОМАТИЧНЕ СЕКЦІОНУВАННЯ РОЗПОДІЛЬНИХ ЕЛЕКТРИЧНИХ МЕРЕЖ НАПРУГОЮ 6−10 КВ ІЗ ЗАСТОСУВАННЯМ РОЗ’ЄДНУВАЧІВ НОВОГО ПОКОЛІННЯ - Буйний , Р.О.; Діхтярук , І.В.; Зорін , В.В. (Інститут електродинаміки НАН України, Київ, 2014)
Approach to the sectionalization of the distributing electrical networks with high voltage of 6–10 kV with the using new generation has been proposed. The amenity of the disconnectors RLK-10 equipped with automatic drive and reclosers РВА/TEL has been analysed for the disconnection of the section of the distribution network where a damage emerged and switching on the reserve source. The effectiveness of using such switching device as disconnector RLK-10 with a drive for the automatic disconnection of the damage section. Approach to the automation of the distribution networks wich has been proposed in this work will significantly reduce the cost of finding and fault location in distribution systems, lower operating costs and reduce the time required for recovery of power supply to a minimum. References 7, figures 5.